Gilles Deleuze i Michel Foucault o platońskim polityku. Od pozorów prawdy do krytyki władzy = Gilles Deleuze and Michel Foucault on Plato`s statesman. From appearances of truth to the critic of power - Jakimowska, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
That property of the world, the possibility of simulating its reference to an objective reality concealed behind language means that the idea of Truth is exceptionally sensitive to political exploitation. According to post-modernists, Nietzsche is the precursor of this approach. He examined the political interests concealed behind the desire to tell the "truth" to other people, and also of imposing it on them by force.
Keywords: postmodernizm; pozór; simulacrum; mimesis; metadyskurs; blokowanie; ujarzmienie; postmodernism; appearance; metadiscourse; investment; subjugation